Function war: An Evaluation of Encode project and Junk DNA in the light of Philosophy of Biology - Rahman, Atikur (Cosmos and History: The Journal of Natural and Social Philosophy, 2024)
For a large period of time in biology, it was thought that only 1-2% of the entire human DNA carries protein-making signals, and the remaining 98% of DNA does not carry protein-making signals. They were called junk DNA or non-coding DNA. The Encode Project began in 2003 to explore the function of the remaining 98% of human DNA in the context of human genome research. From the ENCODE project of 2007 and 2012, we know that about 80% of the DNA in the human body is not junk. The subsequent criticisms of the Encode project have been numerous. But no matter the criticism, the results of the Encode Project have always proved true. In this paper I will evaluate the result of Encode project for the case of junk Dna in the light of philosophy of biology.